2021
DOI: 10.1002/cam4.4469
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of metastasis and survival between male and female breast cancer with different molecular subtypes: A population‐based observational study

Abstract: Objective: Male breast cancer (BC) is a rare disease, having different clinicopathological features and survival outcomes from female patients. The aim of this research was to, combine with molecular subtypes, analyze the metastatic patterns, and prognosis between male and female patients, and to determine whether the gender was the independent prognostic factor for BC. Methods: Data used in this study were acquired from the SEER database from 2010 to 2016. The clinicopathology features and metastatic patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Their research may help doctors accurately predict the prognoses of patients and develop precise medical treatment plans, further improving prognoses. Studies applying statistical analysis methods to BC found that men with different molecular subtypes with MBCB had very different onset patterns and prognoses [92] . This information facilitates the development of precise treatment plans for patients of all molecular subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Their research may help doctors accurately predict the prognoses of patients and develop precise medical treatment plans, further improving prognoses. Studies applying statistical analysis methods to BC found that men with different molecular subtypes with MBCB had very different onset patterns and prognoses [92] . This information facilitates the development of precise treatment plans for patients of all molecular subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…An observational retrospective study of 53 MBCs by Herrero et al observed that 77% of the patients were former smokers and 17% had history of alcoholism [4]. A SEER-based analysis of 1704 MBCs and 225,417 FBCs from 2010 to 2016 by Fang et al observed that MBCs had older age and a higher rate of Black race [8].…”
Section: Methodsmentioning
confidence: 99%
“…MBCs also had higher incidence of distant metastases at the time of diagnosis (5.93% vs. 4.12% in FBCs), with bone being the most common metastatic site (85.29%). Hormone-/HER2-had the highest distant metastatic rate in MBC (21.26%) [8]. Elimimian et al, in their analysis of MBCs and FBCs in National Cancer Database (NCDB), observed that male patients presented with later clinical staging and exhibit worse disease grade and worse comorbidity scores.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [ 10 ] investigated the influence of age at diagnosis on metastatic BC and patients’ prognosis, and found that elder BC patients were more likely to have lung metastasis, and they had the worst both overall survival and breast cancer-specific survival comparing to younger patients. A population-based observational study also showed that BC patients with different molecular subtypes had different metastasis patterns and survivorship [ 11 ].…”
Section: Introductionmentioning
confidence: 99%